Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Di SMK Sirajul Falah - Rizky Ramadhani; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
SMK Sirajul Falah is one of the institutions in the world of education. SMK Sirajul Falah was founded in 2010, which is located at Jl. H. Mawi RT. 02/01 No. 42, Bojong Indah, Kec. Parung, Kab. Bogor Prov. The problems faced are the registration of new students who still use manual methods and the lack of information media in the introduction of SMK Sirajul Falah. Therefore, with the creation of this website, it is hoped that the Sirajul Falah Vocational School can provide information easily. Making this website using CMS Wordpress with AMD Ryzen 5 3500U Proccesor hardware (8 CPUs) ~ 2.1GHz, 2.00GB RAM, as well as Microsoft Office Professional 2019 and Windows 10 Home Single Language software. The result of this research is a website that is easy to convey information about SMK Sirajul Falah. The tests carried out are blackbox testing and also questionnaires to teachers and the general public. The results of the test show that all menus on the website are running well, the respondents also stated that the Sirajul Falah Vocational School website is good and easy to understand. The design of this website is expected to help the introduction of SMK Sirajul Falah to the general public.